Abigail : a novel - Smith, Jill Eileen, 1958- (Smith, Jill Eileen, 1958- Wives of King David, 2010)
Abigail tries to honor and respect her husband Nabal despite his abuse of her, but when he suddenly dies, Abigail is free to move on with her life--a life that includes a new husband, David, who insists on having several wives.